Association between sulfur microbial diet and the risk of dementia: a large-scale prospective cohort study - Jigen Na; Celi Yang; Muzi Na; Xiaona Na; Yuefeng Tan; Xiaojin Shi; Zhihui Li; John S. Ji; Ai Zhao (Nutrition Journal)
Abstract Background The sulfur microbial diet (SMD), a dietary pattern linked to sulfur-metabolizing gut bacteria, has been associated with metabolic disorders. However, its role in dementia risk remains unclear. Methods This prospective cohort study investigated the association between SMD and dementia risk and examined potential mechanisms. We included 125,714 UK Biobank participants who completed at least two 24-hour dietary recalls. SMD scores were calculated based on food intake associated with sulfur-metabolizing bacteria. The primary outcome was incident dementia, including Alzheimer’s disease (AD), vascular dementia (VD), and frontotemporal dementia (FTD). Secondary outcomes included cognitive function and brain volume changes. Cox proportional hazards models were employed to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Stratified and mediation analyses were conducted to explore potential population heterogeneity and mechanisms. Results Over a median follow-up of 8.58 years, 691 dementia cases occurred. A U-shaped association was observed between SMD scores and the risk of dementia and AD. Compared with the middle quintile, participants in the highest quintile had a 37% higher dementia risk (HR = 1.37, 95% CI: 1.08–1.74) and a 46% higher AD risk (HR = 1.46, 95% CI: 1.00–2.14). No significant association was found for the lowest quintile. Associations were stronger in males and older adults. Diabetes mediated 8% of the total effect of high SMD adherence on dementia risk. No significant associations were observed for VD and FTD. Cognitive function changes were not notable. Higher SMD adherence was linked to reduced thalamic grey matter volume, while lower adherence was associated with increased volume in the precentral and postcentral gyri. Conclusions A U-shaped relationship exists between SMD and dementia risk, particularly AD, with potential sex- and age-specific differences. Diabetes may partly mediate this association. SMD may also affect brain volume. These findings suggest a possible role of SMD in the diet-microbiota-gut-brain axis and neurodegeneration.